Pragmatics, education and argumentation: Introduction to the special issue. (October 2022) - Rapanta, Chrysi; Macagno, Fabrizio
Abstract: The analysis of how context affects meaning, and how utterances affect a conversational situation is a fundamental and little acknowledged dimension of educational and argumentative dialogues. Pragmatics is presupposed by any discipline addressing how dialogic teaching affects learning or how argumentative dialogues can improve critical thinking skills. Pragmatics is underlying the study of arguments conceived not only as logical constructs but as means for resolving conflicts, differences, or doubts in different contexts and of different types. Pragmatic is the type of analysis that is often conducted in the areas of education and argumentation when dialogues are coded according to the function of utterances that constitute them, assessed based on their relevance or the cohesion between their parts, or studied in their implicit components and messages. Overall, pragmatics is the hidden dimension of many educational studies in argumentation and education, and one of the tenets of argumentation theory. However, no explicit consideration of the pragmatic dimensions of educational dialogue, especially the argumentative one(s), is currently present in the literature. The hidden and crucial relation between pragmatics, education, and argumentation is the subject matter of this special issue, and the tentative to make it explicit.